Implementation of Prototype Solar-Powered Wireless Electric Vehicle Charging Station - JUSMAN, DAMIA AMANINA; Lam, Hong Yin (Progress in Engineering Application and Technology, 2026)
The rapid adoption of electric vehicles (EVs) has increased the demand for efficient, safe, and sustainable charging infrastructure. Conventional conductive EV charging systems rely on physical connectors, which are prone to corrosion, safety risks, and high maintenance requirements, particularly in tropical climates. In addition, grid-dependent charging contributes to peak load stress and continued reliance on fossil fuel-based electricity generation. This study presents the development of a prototype solar-powered wireless electric vehicle charging station integrated with an intelligent control and monitoring system. The proposed system combines photovoltaic energy harvesting, resonant inductive wireless power transfer, and an Arduino-based control unit with Internet of Things (IoT) monitoring capabilities. Vehicle detection and authorization are achieved using infrared and RFID sensors, while a servo-assisted alignment mechanism ensures efficient energy transfer between transmitter and receiver coils. Real-time monitoring of voltage, current, temperature, and battery state-of-charge is implemented through a cloud-based interface. Experimental results demonstrate that the system can achieve wireless power transfer efficiency of up to 71.6% under optimal alignment conditions while operating independently from the electrical grid. The integration of solar energy reduces grid dependency and supports sustainable mobility initiatives. Overall, the prototype validates the feasibility of a compact, renewable-powered, wireless EV charging solution suitable for small-scale applications and future expansion toward smart charging infrastructure.